The functional expression and characterisation of a cysteine peptidase from the invasive stage of the neuropathogenic schistosome Trichobilharzia regenti - Dolecková, Katerina; Kasný, Martin; Mikes, Libor; Cartwright, Jared; Jedelský, Petr; Schneider, Eric L; Dvorák, Jan; Mountford, Adrian P; Craik, Charles S; Horák, Petr (International journal for parasitology, 2009)
A transcriptional product of a gene encoding cathepsin B-like peptidase in the bird schistosome Trichobilharzia regenti was identified and cloned. The enzyme was named TrCB2 due to its 77% sequence similarity to cathepsin B2 from the important human parasite Schistosoma mansoni. The zymogen was expressed in the methylotropic yeast Pichia pastoris; procathepsin B2 underwent self-processing in yeast media. The peptidolytic activity of the recombinant enzyme was characterised using synthetic fluorogenic peptide substrates at optimal pH 6.0. Functional studies using different specific inhibitors proved the typical cathepsin B-like nature of the enzyme. The S(2) subsite specificity profile of recombinant TrCB2 was obtained. Using monospecific antibodies against the recombinant enzyme, the presence of cathepsin B2 was confirmed in extracts from cercariae (infective stage) and schistosomula (early post-cercarial stage) of T. regenti on Western blots. Also, cross-reactivity was observed between T. regenti and S. mansoni cathepsins B2 in extracts of cercariae, schistosomula or adults. In T. regenti, the antisera localised the enzyme to post-acetabular penetration glands of cercariae implying an important role in the penetration of host skin. The ability of recombinant TrCB2 to degrade skin, serum and nervous tissue proteins was evident. Elastinolytic activity suggests that the enzyme might functionally substitute the histolytic role of the serine class elastase known from S. mansoni and Schistosoma haematobium but not found in Schistosoma japonicum or in bird schistosomes.
Keywords: Cattle; Turkeys; kathepsin B; western blotting; skot; cystein; myši inbrední BALB C; molekulární sekvence - údaje; Amino Acid Sequence; hlemýždi; králíci; Mice, Inbred BALB C; Blotting, Western; Schistosoma; substrátová specifita; Animals; lidé; cysteinové proteasy; kachny; Humans; Substrate Specificity; zvířata; Rabbits; Cysteine Proteases; sekvence aminokyselin; myši; Snails; Molecular Sequence Data; Cathepsin B; Mice; krocani; Cysteine; Schistosoma mansoni; Pichia; Ducks